Smart cities: potential and challenges - Zanella, Andrea (2019)
This paper aims to discuss a few fundamental questions related to the smart city paradigm, such as “what is actually a smart city?”, “what can we expect from a smart city?”, and “which problems have to be addressed and solved in order to turn a standard (dumb) city into a smart one?” Starting from a discussion of the Smart City concept, we will illustrate some of the most popular smart services using the results of proof-of-concept experiments carried out in different cities around the world. Successively, we will describe the fundamental functions required to build a smart service and the corresponding enabling technologies. We will then describe the main research challenges that need to be addressed in order to fulfill the Smart City vision, and we will conclude with some final remarks and considerations about the possible evolution of the Smart City concept.